Systematic evaluation of lithium-excess polyanionic compounds as multi-electron reaction cathodes. Issue 36 (9th September 2019) - Li, Ruhong; Liu, Jianchao; Chen, Tianrui; Dai, Changsong; Jiang, Ningyi
Abstract : The findings provide a comprehensive understanding of defect/electronic structure/ion transport and intrinsic properties of polyanionic Li3 V2 (PO4 )3 . Abstract : Polyanion cathodes with multi-electron redox always facilitate wider application in a metal ion-based battery system because of their high capacity and safety. However, the irreversible phase transformation and interfacial deterioration remain major impediments. Herein, using monoclinic Li3 V2 (PO4 )3 as a model, the impact of excess lithium on its electrochemical properties are demonstrated. It was determined that a maximum of 5% excess lithium could be incorporated into the monoclinic structure, and a further overdose of lithium led to the formation of secondary phase Li3 PO4 . The excess Li + ions are located at both octahedral and interstitial sites, which enable enhanced redox kinetics that are mainly attributed to accelerated ionic movement induced by alternate diffusion behavior of Li + ions in a three-dimensional permeation path. Moreover, Li-excess local configurations can stabilize the lattice oxygen and provide a favorable cathode–electrolyte interface, which synergistically relieves the structural degradation during electrochemical cycling, thus guaranteeing exceptional cycling stability ( e.g., 82.5% after 1000 cycles at 1000 mA g −1 ). These findings provide a comprehensive understanding of defect/electronic structure/ion transport and the intrinsic properties of polyanionic Li3 V2 (PO4 )3 and may help to pave the way for other highly stable electrodes for rechargeable batteries.